2023
DOI: 10.3390/cells12010181
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Oxidant and Pro-Oxidant Effects of Peroxiredoxin 6: A Potential Target in Respiratory Diseases

Abstract: Peroxiredoxin 6 (PRDX6) is widely distributed in several organs, especially the lungs. The role of PRDX6 in oxidative stress is controversial and even contradictory, as indicated by research conducted over the past 20 years. PRDX6 has anti-oxidant or pro-oxidant effects on oxidative stress in different diseases. It can even exhibit both anti-oxidant and pro-oxidant effects in the same disease. These findings are attributed to the fact that PRDX6 is a multifunctional enzyme. The peroxidase and phospholipase A2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…The activation of both transcription factors was corroborated by the enhanced levels of Ifnb and Cxcl10, downstream of both pathways (Figure 2F). Finally, we found that alterations in the IRI group were associated with a decrease in Prdx6 (Figure 2G), an antioxidant protein known to protect against oxidative stress [32,33]. Taken together, these findings suggest that PM 2.5 exposure and IRI act synergistically to enhance inflammation by activating the cGAS–STING pathway, possibly via compromised mitochondrial integrity and oxidative stress in the damaged tubular epithelium.…”
Section: Resultsmentioning
confidence: 78%
“…The activation of both transcription factors was corroborated by the enhanced levels of Ifnb and Cxcl10, downstream of both pathways (Figure 2F). Finally, we found that alterations in the IRI group were associated with a decrease in Prdx6 (Figure 2G), an antioxidant protein known to protect against oxidative stress [32,33]. Taken together, these findings suggest that PM 2.5 exposure and IRI act synergistically to enhance inflammation by activating the cGAS–STING pathway, possibly via compromised mitochondrial integrity and oxidative stress in the damaged tubular epithelium.…”
Section: Resultsmentioning
confidence: 78%
“…The aiPLA2 activity has been confirmed in the deduced amino acids from the nucleotide sequences of clones isolated from a cDNA library of human adult myeloid cells [17,25]. The catalytic triad (S32, H26, and D140) of phospholipase activity resides on the surface of the Prdx6 protein, which plays a pivotal role in the reduction of oxidized phospholipids and cell-membrane remodeling [26]. Research has indicated that the mutations in the His26 and Ser32 of Prdx6 lead to the loss of the ability to bind phospholipids and the aiPLA2 activity.…”
Section: Enzyme Activities and Function Of Prdx6mentioning
confidence: 85%
“…The antioxidant enzymes involved in cellular defence, such as CAT, SOD, PRDX and GPx, are responsible for converting superoxide radicals into water (Sovernigo et al., 2017). The SOD converts the superoxide radical into hydrogen peroxide and oxygen, while CAT, GPx and PRDX convert these radicals into water (Baszyński et al., 2022; Jia et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The SOD converts the superoxide radical into hydrogen peroxide and oxygen, while CAT, GPx and PRDX convert these radicals into water (Baszyński et al, 2022;Jia et al, 2023).…”
Section: Introductionmentioning
confidence: 99%